Pelaksanaan Penyimpanan Rekam Medis Berdasarkan Unsur Manjemen 5M di Puskesmas Medan Johor - Valentina; Winda Andryani Sinaga (Akademi Perekam dan Informasi Kesehatan Imelda, 2021)
The implementation of medical records carried out at the puskesmas requires management in managing all existing activities with the aim of creating good health services, in accordance with procedures and guidelines. To achieve the goal of processing medical records, 5 elements of management are needed, namely man, money, material, machine, and method. The purpose of this study was to determine the management elements of man, money, material, machine, and method in the implementation of medical records carried out at the Medan Johor Health Center. This type of research uses qualitative research methods with a phenomenological approach. The study was conducted from May to July 2020. The population was all medical record officers at the Medan Johor Health Center. The research sample amounted to 5 people who were taken by saturated sampling. The research instrument is an interview guide and recorded using an audio recorder and a check list sheet for observation. The results showed that the man element was 5 people and none of them had a medical record background and had never received training, the money element was the funding obtained from JKN and APBD, the material element was that a family folder was used to store all patient forms, while the use of tracers and register books has not been used to control the borrowed files out of the storage rack, and the filling cabinet is used as a tool to store medical record files, the machine element is a primary care application to register patients, the SIMPUS application is used for reporting, the method element is Not all SOPs in medical records exist. The advice given is to provide training to medical record officers so that their officers better understand the importance of medical records.